Pola Komunikasi Pemuda Hijrah XTC Lingkar melalui Konsep “LIQO” | - Tria Satria Handaya; kiki zakiah darmawan (UNISBA Press, 2022)
Abstract. The phenomenon of migration among the millennial generation was greeted enthusiastically by millennial youths. Starting from the community at the national level to the local level. The rapid flow of migration has drawn pros and cons among the community. Apart from the pros and cons that have emerged, the phenomenon of the wave of migration of millennials is actually a great potential for the awakening of Islam from the millennial generation in Indonesia for the future of the people. XTC Hijrah is a dakwah-based community under XTC Indonesia. In order to form objects that are able to play a role in the midst of society, the XTC Lingkar Hijrah Youth Community has an activity that aims to meet the needs of tarbiyah and deepen knowledge of Islam in community members, this activity is called liqo. The purpose of this research is to find out how the communication patterns of youth migrating XTC Lingkar through the concept of